Climate Justice in Light of the Paris Agreement on Climate Change - Fanous, Hawraa; Abed, Mustafa (Journal of Legal Sciences, 2023)
Climate change poses a difficult challenge to social justice, people are not equally affected by climate change, especially the most vulnerable groups in developing countries because they are least prepared to face the effects of climate change, and the term climate justice is used to consider human rights, equality and historical responsibility in relation to climate change, and concepts of environmental justice can In particular, social justice in general is to achieve climate justice through the implementation of human rights, and within the framework of international efforts to confront climate change, the 2015 Paris Agreement was adopted, which included mechanisms based on transparency and subject to international review, and recognized the principle of compensation for losses and damages to countries most vulnerable to climate change, which are matters It matters most to developing countries.